Riset Hadis Berbasis Multimedia - Yazofa, Tartila (UIN Sumatera Utara Medan, 2023)
This research discusses multimedia-based hadith research in the reception study of living hadith studies in the form of film media. Muslim individuals in the current era are increasingly exploring religious teachings through social media, especially on YouTube. This phenomenon makes contemporary Muslim scholars convey religious teachings more in the form of video lectures and even package them more interestingly in the form of films that contain Islamic teaching values. Mapping multimedia-based hadith research, one of which focuses on the soap opera